216-35: Performance of the RYTHMIQ(TM) algorithm to minimize right ventricular pacing: a multicenter study. (10th June 2016) - Strik, Marc; Defaye, Pascal; Eschalier, Romain; Mondoly, Pierre; Antonio, Frontera; Ritter, Philippe; Haïssaguerre, Michel; Ploux, Sylvain; Ellenbogen, Kenneth; Bordachar, Pierre
Abstract: Background: In Boston Scientific dual-chamber devices, the RYTHMIQ(TM) algorithm aims to minimize RV pacing. We evaluated its performance by determining 1) the appropriateness of the switch from the AAI(R) with backup VVI pacing to the DDD(R) mode in case of suspected loss of AV conduction and 2) the rate of recorded pacemaker mediated tachycardia (PMT) when AV hysteresis searches for restored AV conduction. Methods: We included 157 patients from 4 centers with a Boston Scientific dual chamber pacemaker (40) or ICD (117) without permanent AV conduction disorder and with RYTHMIQ enabled. We reviewed the last 10 remote monitoring-transmitted EGMs of RYTHMIQ switch and of PMT episodes. Results: 142 patients (90%) demonstrated ≥1 episode of RYTHMIQ switch. Of 1266 episodes: 16% were appropriate (loss of AV conduction) while 84% were inappropriate: 66% was related to compensatory pause (PVC 56% [FIG 1], PAC 7% or both 3%) or to a PVC falling in the post-atrial pacing ventricular refractory period interval (21%) and 10% were related to lead dysfunction (atrial or ventricular undersensing, atrial capture failure or atrial noise oversensing). The average time spent in DDD(R) mode after an inappropriate switch episode was 4h48m (median 1m03s, 46s to 289h). 154 PMT episodes were diagnosed in 27 patients (17%). In 69% of correctly diagnosed episodes, the onset of PMT was directly related to the algorithm related prolongation of the AV delay promoting AV dissociation and retrograde conduction. Conclusion: The RYTHMIQ algorithm shows: 1) high rate of inappropriate switch (mostly PVCs) and 2) high rate of induction of PMT. This may have clinical implications in terms of selection of the patients and may suggest required changes in the algorithm architecture.